SCREENING OF PHYTOCHEMICALS AND IN VITRO ANTIOXIDANT ANALYSIS OF IXORA MACROTHYRSA (TEJISM. AND BINN.) - SARASWATHI G, SURUTHI; DOSS D, VICTOR AROKIA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the study was to investigate the phytochemical screening and quantitative and in vitro antioxidant analysis of the hydroethanolic leaf extract of Ixora macrothyrsa (Tejism. and Binn.) Methods: The powdered plant material was extracted using different solvents for phytochemical screening. For the quantitative analysis, proteins, carbohydrates, tannins, free amino acids, and proline were estimated. In vitro antioxidants such as ascorbic acid, total phenols, chlorophyll, and carotenoids were also analyzed using standard methods. Results: The preliminary qualitative analysis of the hydroethanolic leaf extract of I. macrothyrsa showed the presence of carbohydrates, proteins, alkaloids, flavonoids, phenols, saponins, glycosides, and tannins. The secondary metabolites such as proteins, carbohydrates, tannin, free amino acid, and proline were quantified as 24.57±0.61 mg/g, 11.07±0.09 mg/g, 6.17±0.20 mg/g, 9.20±0.17 mg/g, and 34.47±0.44 mg/g, respectively. In vitro antioxidants such as ascorbic acid, total phenols, chlorophyll, and carotenoid were estimated to be 35.73±0.28 mg/g, 15.9±0. mg/g, 9.33±0.09 mg/g, and 5.9±0.58 mg/g, respectively. Conclusion: It can be concluded that the hydroethanolic extract of the leaves of I. macrothyrsa showed the presence of major secondary metabolites and has potent antioxidant activity.